Analisis Gejala Hiperbola pada Merek Dagang dan Slogan Produk Makanan PT. Indofood - Budhiarno, Claudin Arfienka Budhiarno; Assidik, Gallant Karunia (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
Symptoms of hyperbole on the food trademark PT. Indofood is very interesting to study. This is due to the discovery of the use of hyperbole which is quite unique in one of PT. Indofood's products, namely Qtella. The location of the hyperbole language style on the brand is the use of the letter Q as a pronoun for the word Ketela. In addition, Qtella products also have the slogan 'The master of family snacks'. Therefore, the researcher wants to study further about other findings regarding the symptoms of hyperbole in the trademarks and slogans of PT. Indofood's food products. The purpose of this study is to find out how the symptoms of hyperbole on the trademark and slogan of PT. Indofood's food products and their impact. The method used in this research is descriptive analytical method. This study uses an analysis of the meaning of language style. Data collection in this study was carried out by observing and taking notes. That is, the data in this study was obtained by observing trademarks or products produced by PT. Indofood Indonesia and then recording advertising data containing language styles. First, the slogans and trademarks were observed, after that the advertisements containing the language style were selected. Based on the results of the study, conclusions can be drawn, namely hyperbole symptoms in PT. Indofood's trademarks and food product slogans are classified into 4 hyperbole symptoms, namely typographic hyperbole, meaning hyperbole, image hyperbole, and pronunciation hyperbole.